Design and Performance Analysis of a Dual Band Patch Antenna and its MIMO Implementation for Wi-Fi, Radar, and V2X Applications - Singh, P. P.; Sharma, S. K.; Gupta, N. (Advanced electromagnetics, 2025)
A dual-band 2-port Multiple Input Multiple Output (MIMO) antenna is designed and analyzed in this paper. The designed antenna resonates at two frequencies, 4.54 GHz and 5.8 GHz, with bandwidths of 340 and 360 MHz for each band, respectively. A low-cost FR-4 substrate with a dielectric constant of 4.4 and a thickness of 1.6 mm is used to simulate and fabricate the antenna. Total dimension of a single antenna element is 17 mm×22 mm×1.6 mm (0.25λ×0.32λ×0.024λ), and the MIMO configuration measures 45 mm×22 mm×1.6 mm (0.66λ×0.32λ×0.024λ) at 3.6 GHz. The fundamental parameters of MIMO antenna like isolation (>20dB), ECC (<0.00012), DG (~10), MEG (-3dB), CCL (<0.2 bps/Hz) and TARC (<0.3) and radiation parameters are evaluated which prove the practicality of the antenna for Wi-Fi (5.725-5.85 GHz), 5G applications in Japan (4.4-4.5 GHz), radar (civilian and military), amateur radio communications (5.65-5.925 GHz), and Vehicle-to-Everything (V2X) (5.85-5.925 GHz) communication systems. Also, the designed antenna demonstrates radiation efficiency of more than 69% across first operating band and more than 76% across second operating frequency. The designed antenna can also be used in remote sensing applications to study various environmental parameters at 4.54 GHz, as electromagnetic waves at this frequency penetrate easily and provide data on soil moisture, vegetation, etc.